2016
DOI: 10.21608/bvmj.2016.31283
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological and molecular studies on toxigenic Clostridium perfringens in milk and some milk products

Abstract: Two hundred random samples of milk, kareish cheese, yoghurt and ice-cream (50 for each) were examined microbiologically for the presence of Clostridium perfringens, their enterotoxigencity and their antibiotic sensitivity. Clostridium perfringens was isolated from 3 (6%) milk samples, 4 (8%) kareish cheese samples and it could not be isolated from any examined samples of yoghurt and ice-cream. The majority of C. perfringens isolates recovered from milk and milk products were susceptible to ofloxacin, ampicilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…The cpa gene was found in all C. perfringens isolates in our study indicating the predominance of type A strains. This is consistent with other researches (Abd El Tawab et al, 2016;Akhi et al, 2015;Osama et al, 2015). Type A is usually isolated from the intestine of apparently healthy humans and animals, therefore, it's a role in pathogenicity is controversy (Fernandez-Miyakawa and Redondo, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The cpa gene was found in all C. perfringens isolates in our study indicating the predominance of type A strains. This is consistent with other researches (Abd El Tawab et al, 2016;Akhi et al, 2015;Osama et al, 2015). Type A is usually isolated from the intestine of apparently healthy humans and animals, therefore, it's a role in pathogenicity is controversy (Fernandez-Miyakawa and Redondo, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, C. perfringens was identified in 6.7% buffalo milk, 3.3% cow milk and 5% camel milk. These findings are comparable with 6% reported from raw milk samples in Egypt (Abd El Tawab et al, 2016). Another study in Egypt reported the isolation of C. perfringens from 4.5% (16/357) of cow milk samples and 4% (1/25) from buffalo milk (Osman et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations